Formulation and Evaluation of Atenolol Microspheres - V. T. ISWARIYA, T.V.V.S Sahithi, A. Maheswari, K. Madhu, K. Maryswarnalatha (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of present study is to formulate and evaluate atenolol microspheres using excipients like sodium alginate, calcium chloride and starch soluble. Method: The encapsulation efficiency was higher in formulations with higher polymer concentrations than in the other nine. In order to make microspheres, the ionotropic gelation method was used. High yielding and easy to produce, this technology represents a significant improvement over current procedures. Conclusion: A granulometric research, bulk and tapped density, mean particle size and angle of repose, drug entrapment efficiency and in-vitro dissolution study were all found to be within acceptable limits in terms of their results